Reduced efficacy of fluazinam against Phytophthora infestans in the Netherlands - Schepers, Huub; Kessel, Geert Jan; Lucca, Ana Maria Florencia; Förch, M.; van den Bosch, G.B.; Topper, Corina; Evenhuis, A. (Springer Nature, 2019)
Phytophthora infestans is the causal organism of potato late blight, the most important disease in potato, the second most important arable crop in Europe. The P. infestans population in Europe is well known for its sudden changes in composition. Currently it is composed of a wide variety of genotypes, some of which are dominant clonal lines while others are rare or even unique to a year or location. Fungicides play a crucial role in the integrated control of late blight. Since its introduction in the Netherlands in 1992, fluazinam has been used in late blight control strategies in ware and starch potatoes. It has a broad spectrum of activity and is effective against a range of diseases including potato late blight. Fluazinam interrupts the pathogen cell’s energy production process by an uncoupling effect on oxidative phosphorylation. It is considered to have a low resistance risk. Until recently, reduced efficacy against fluazinam was not detected in P. infestans surveys in Europe. In this paper we present the finding of a new clonal lineage (EU_33_A2) of P. infestans in the Netherlands and the reduced efficacy of fluazinam to control one of the EU_33_A2 isolates in field experiments carried out in 2011 and 2015 under high disease pressure. The potential effects of this finding on practical late blight control strategies are discussed.